Involvement of Local Communities in the Development of Batulayang Tourism Village - Awaloedin, Dipa Teruna; Fitri, Novita Iza; Putra, Suadi Sapta; Pradini, Gagih (International Journal of Education, Information Technology, and Others, 2024)
This abstract examines the involvement of the local community in the development of Batulayang Tourist Village, a tourism-focused village in the Cisarua district of Bogor. The study employs a qualitative approach with a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in the village's development. The results indicate that Batulayang Tourist Village possesses strengths in its natural beauty and cultural richness, along with active community participation in tourism development and management. However, there are weaknesses, such as inadequate infrastructure, a lack of community awareness of tourism potential, and insufficient destination promotion. Opportunities for growth include collaborations with private sector entities, skill development for the community, and the introduction of new tourism products. The threats faced include competition from other tourist villages and potential negative impacts on the environment and local culture. The study concludes that active community participation is key to the successful development of Batulayang Tourist Village, as it drives economic growth, cultural preservation, and environmental sustainability. Recommendations for improvement include providing training and support for community members in tourism-related skills, forming cooperatives or joint business groups, and involving the community in the planning and management of tourism in a sustainable manner.